Kadar Flavonoid, Senyawa Biomarker Antikanker pada Tumbuhan Famili Asteraceae dari Daerah Kopeng Kabupaten Semarang Indonesia - Elizabeth Betty Elok Kristiani; Sri Kasmiyati (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
The Asteraceae family plants are reported to have various abilities as drugs. Artemisia belongs to the Asteraceae family has been used as a drug for malaria, and recent developments have been studied for its ability as anticancer agents. Cosmos caudatus, a member of the Asteraceae family that believed by many people for its ability to heal cancer. The aims of this study were to determine the content of quercetin, kaempferol, and artemisinin which is an anticancer biomarker compound in A. annua, A. vulgaris Linn., A. chinese Berg ex Poljakov, and Cosmos caudatus Kunth which grow in Kopeng blood, Semarang Regency, Province Central Java. The plant samples were dried and mashed up. The content of biomarker compounds was determined using using High Performance Liquid Chromatography (HPLC). The artemisinin levels in A. annua, A. vulgaris Linn., A. cina Berg Poljakov, and Cosmos caudatus Kunth were 0.2800; 0.3000; 0.1700; and 0.0300% respectively. The kaempferol was detected in the three Artemisia were 0.2987; 0.0013; and 0.0074%. In all four plants, quercetin was only detected in A. annua.